2016
DOI: 10.1111/jpm.12304
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Body Wraps in Swiss public adult acute inpatient wards. A retrospective descriptive cohort study

Abstract: Introduction Many patients suffering from serious mental illness experience severe anxiety and those with psychosis often report the feeling of their bodies falling apart. While it is believed that these patients benefit from therapeutic body wraps (TBWs), the use of this adjunct therapy has rarely been studied in adult patients. Aims The aim of this study was to obtain descriptive statistics on the clinical, social-demographic and institutional reality of TBW therapy in Swiss public adult inpatient wards. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…This is due to the fact that the inpatient stays are presently very limited in time and that the therapeutic teams are reluctant to initiate psychobody approaches that are deemed incompatible with short stays and time consuming for the hospital clinical staff. A quantitative inquiry (Opsommer et al, 2016) showed that TBWs are mainly offered to patients diagnosed either with any of the DSM IV TR diagnostic categories within F20-29 or F30-39 groups, which makes them a potentially difficult target group to include in a study directly following an inward episode. Three persons initially agreed to be interviewed and eventually declined when contacted by the interviewer after the discharge from hospital.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to the fact that the inpatient stays are presently very limited in time and that the therapeutic teams are reluctant to initiate psychobody approaches that are deemed incompatible with short stays and time consuming for the hospital clinical staff. A quantitative inquiry (Opsommer et al, 2016) showed that TBWs are mainly offered to patients diagnosed either with any of the DSM IV TR diagnostic categories within F20-29 or F30-39 groups, which makes them a potentially difficult target group to include in a study directly following an inward episode. Three persons initially agreed to be interviewed and eventually declined when contacted by the interviewer after the discharge from hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The patient's entire body, except the face area, is tightly wrapped in wet cold sheets (below 60°F/15°C) and covered by blankets. As documented by Opsommer et al (2016), TBW clinical teams are composed mostly by two psychiatric nurses, a nurse and a psychiatrist and, less frequently, by any of the latter two and a clinical psychologist. Two clinicians take seats on either side of the patient's bed, should the patient wish to communicate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the era of efficient treatment (e.g., antipsychotics; ECT) for adult psychosis, TBW tended to become anecdotal. More recently, TBW was used in adult psychiatric inpatients as an alternative to physical constraints [ 12 ] or to control anxiety [ 13 ]. Interestingly, in the largest recent retrospective study, which included 172 cases, TBW showed potential to reduce the dose of both anxiolytic and antipsychotic drugs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%